2015
DOI: 10.3758/s13423-015-0915-3
|View full text |Cite
|
Sign up to set email alerts
|

Perception and action influences on discrete and reciprocal bimanual coordination

Abstract: For nearly four decades bimanual coordination, Ba prototype of complex motor skills^and apparent Bwindow into the design of the brain,^has been intensively studied. Past research has focused on describing and modeling the constraints that allow the production of some coordination patterns while limiting effective performance of other bimanual coordination patterns. More recently researchers have identified a coalition of perception-action constraints that hinder the effective production of bimanual skills. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 171 publications
4
46
0
Order By: Relevance
“…Implicit in studies examining bimanual coordination is that there are two stable coordination modes: in-and anti-phase (Kelso, 1995;Shea, Buchanan, & Kennedy, 2015). Perceptual information can be manipulated in ways so as to make complex rhythmic tasks more easily accessible to the performer (Kovacs et al, 2009;Mechsner, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Implicit in studies examining bimanual coordination is that there are two stable coordination modes: in-and anti-phase (Kelso, 1995;Shea, Buchanan, & Kennedy, 2015). Perceptual information can be manipulated in ways so as to make complex rhythmic tasks more easily accessible to the performer (Kovacs et al, 2009;Mechsner, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the prevalence of aberrant somatosensory processing is high in individuals with ASD and other neurodevelopmental disorders (48)(49)(50), and our study offers a tractable paradigm for exploring potential links between aberrant touch and alterations in contextual modulation. Future studies with neurotypical and clinical populations must also address how bimanual contextual modulation interacts with and supports bimanual motor control (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…However, later studies also demonstrated a role of perceptual factors (Brandes, Rezvani, & Heed, 2016;Heed & Röder, 2014;Oliveira & Ivry, 2008;Swinnen et al, 1998;Temprado, Swinnen, Carson, Tourment, & Laurent, 2003; for review, see Shea, Buchanan, & Kennedy, 2016). For instance, when the index fingers are wiggled with one hand turned up, and the other down, symmetrical movements are still performed more successfully than parallel ones, although they now require concurrent activation of non-homologous muscles (Brandes et al, 2017;Heed & Röder, 2014;Mechsner et al, 2001).…”
Section: Bimanual Coordinationmentioning
confidence: 99%